A demonstrator for measurement workflows using digital calibration certificates (DCCs). (December 2021) - Bruns, Thomas; Nordholz, Jan; Röske, Dirk; Schrader, Thorsten
Abstract: Based on the existing specifications for digital calibration certificates (DCCs), this work presents two approaches to using DCCs in a fully digitised workflow. It shows the basic methods needed to access, edit and deposit DCCs in either a web repository or a file system. These methods are introduced to the reader in examples using Excel macros based on Visual Basic for Applications (VBA) or the Python 3 programming language, meaning that they can be used immediately.